1990
DOI: 10.1063/1.103434
|View full text |Cite
|
Sign up to set email alerts
|

Self-developing holographic recording in Li-implanted Te thin films

Abstract: Ablative holographic recording was performed on Li-implanted Te thin films using a Nd:YAG laser. Implantation doses ranging from 2.9×1013 to 2.3×1015 ions/cm2 within the thin films were seen to produce an increase of the writing threshold by 20% and a reduction of the diffraction efficiency of the recorded gratings at the highest doses. For doses as low as 1.2×1014 ions/cm2, a considerable increase in the stability of the recording media has been observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

1997
1997
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 11 publications
0
20
0
1
Order By: Relevance
“…[4] Trigonal tellurium exhibits many useful and interesting properties for example, photoconductivity and catalytic activity toward some reactions, thermoelectricity, high piezoelectricity and nonlinear optical responses. [5] In the past decade, 1D tellurium nanocrystals have been synthesised by different routes such as solvothermal or hydrothermal methods, [6] microwave-assisted methods, [7] chemical (physical) vapour deposition [8] etc. Xia and coworkers first reported that Te nanotubes with blocking seeds (Te atom clusters) within could be obtained by adding orthotelluric acid to pure ethylene glycol heated to reflux at 197°C.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Trigonal tellurium exhibits many useful and interesting properties for example, photoconductivity and catalytic activity toward some reactions, thermoelectricity, high piezoelectricity and nonlinear optical responses. [5] In the past decade, 1D tellurium nanocrystals have been synthesised by different routes such as solvothermal or hydrothermal methods, [6] microwave-assisted methods, [7] chemical (physical) vapour deposition [8] etc. Xia and coworkers first reported that Te nanotubes with blocking seeds (Te atom clusters) within could be obtained by adding orthotelluric acid to pure ethylene glycol heated to reflux at 197°C.…”
Section: Introductionmentioning
confidence: 99%
“…[40]. L'implantation avec le lithium peut avoir un effet salutaire sur la stabilité de tels films enregistreurs dont le comportement a été suivi sur une période de deux ans [41].…”
Section: Matériaux Optiques Avancésunclassified
“…As a typical semiconductor, Te-I has a narrow direct band gap (band gap energy 0.35 eV) at ambient conditions. It exhibits many unique properties such as photoconductivity, catalytic activity, piezoelectricity, thermoelectricity, and nonlinear optical responses, [8][9][10][11] which make it a multifunctional material in many electric and optoelectronic devices, such as self-developing holographic recording devices, radiative cooling devices, gas sensors, field-effect devices, and infrared acousto-optic deflectors. [10,12,13] Besides, the controlled growth of multi-morphology Te crystals (such as onedimensional nanorods and nanowires, and two-dimensional hierarchical flowerlike microarchitecture) [11,[14][15][16][17][18][19] has developed maturely, which makes it possible to be used in nanodevices.…”
Section: Introductionmentioning
confidence: 99%